Circular RNA Expression Profiling Identifies Glaucoma-Related Circular RNAs in Various Chronic Ocular Hypertension Rat Models - Chen, Xiaoxiao; Zhou, Rongmei; Shan, Kun; Sun, Yanan; Yan, Biao; Sun, Xinghuai; Wang, Jiajian (Frontiers in Genetics, 2020)
Circular RNAs are characterized as a class of covalently closed circular RNA transcripts and are associated with a variety of cellular processes and neurological diseases by sponging microRNAs. Expression profiling of circular RNAs in glaucoma, which is a form of optic neuropathy, has not been performed to date. The most common characteristic of all forms of glaucoma is the loss of retinal ganglion cells. While the pathogenesis of glaucoma is not fully understood, intraocular pressure is unquestionably the only proven modifiable factor which makes chronic ocular hypertension animals the classical glaucoma models. Based on these findings, we completed the first in-depth study of rat retinal circular RNA expression profiling to identify probable biomarkers for the diagnosis of glaucoma. Two ocular hypertension models were induced by episcleral vein ligation and microbead injection in rats. Overall, 15,819 circular RNA were detected. Furthermore, 3,502 differentially expressed circular RNAs verified in both chronic ocular hypertension rats were identified, of which 691 were upregulated and 2,811 were downregulated. Seven significantly downregulated (both log2FoldChange < -2.5 and adjusted P < 0.001) and seven significantly upregulated (both log2FoldChange > 2.5 and adjusted P < 0.001) circular RNAs were shown. Six target microRNAs aligned with the top 14 circular RNAs were identified. According to the construction of the circular RNA-microRNA network and circBase information, only RNO_CIRCpedia_1775 had the homologous hsa_circ_0023826 in the human genome. The hsa_circ_0023826 and mRNA of the host gene TENM4 (teneurin transmembrane protein 4) were validated in aqueous humor samples of five glaucoma patients and five cataract control patients. The expression of hsa_circ_0023826 showed a significant decrease in glaucoma patients, while TENM4 mRNA showed no significant difference compared to cataract patients (P = 0.024 and P = 0.294, respectively). The results of this study comprehensively characterized the expression profiles of circular RNA in glaucoma-affected eyes, as verified by two different ocular hypertension rat models. Together with the target microRNAs underlying the top differentially expressed circular RNAs, a new target of hsa_circ_0023826 and its host gene TENM4 were identified and further verified in the aqueous humor of glaucoma patients, indicating a promising biomarker for the disease.